Lessons from the field: The role of agility in a coproduction project encompassing the COVID‐19 pandemic - Rebecca Pritchard; Sonal Bhavsar; Pamela Campbell‐Morris; Prafulla Modi; Marie Nugent; Jason Hughes (Wiley, 2022)
Abstract Aim We reflect on our experiences of coproducing a redesigned, COVID‐safe priority‐setting activity at a time of shifting priorities and upheaval to gain insight into good practice. Method The project team documented the experience of adapting to COVID‐19 through the reflective project evaluation. We reflect on how COVID disrupted coproduction through radically shifting personal and professional priorities and the implications for good practice. Results Our experiences highlighted the role of agility, management capacity, social capital and power in coproduction. Conclusions COVID‐19 disrupted and enabled coproduction, compounding tensions and serving as the basis to transcend them. The pandemic created new demands on institutions that initially prompted withdrawal to established power, and team members which redefined them in relation to each other. Shifting priorities and demands forced team members into new, and out of former, roles coming into conflict with enduring power dynamics articulating constructs of expertise and authority in the institutional structure. We consider how the tensions found expression: as governance and human resource concerns, problems with authorizing payments, challenges in institutionally accommodating community researchers and the exclusion of some from participation.